DETERMINAN KEPATUHAN PEMBAYARAN WAJIB PAJAK KENDARAAN BERMOTOR (STUDI KASUS PADA KANTOR SAMSAT PEKANBARU KOTA) - Nurhanza Fitri; Dwi Fionasari; R. Septian Armel (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2024)
Abstract: This study aims to obtain empirical evidence of the effect of understanding tax regulations, taxpayer awareness, public service accountability and moral obligation on taxpayer compliance. The population in this study were all motorized vehicle taxpayers who were registered at the joint office of SAMSAT Pekanbaru City. The sampling technique in this study used the random sampling method. The data analysis technique used multiple linear regression analysis techniques. The number of samples in this study were 398 respondents who were taxpayers of motorized vehicles. The software used for data processing is SPSS version 25 for windows. The results of hypothesis testing are as follows. Partially, understanding tax regulations, taxpayer awareness, public service quality and moral obligation to taxpayer compliance. Keywords: Taxpayer Compliance, Understanding of Tax Regulations, Taxpayer Awareness, Public Service Quality, Moral Obligation.